Evaluation of Patients Satisfaction following Caesarean Section in a Secondary level District Hospital (Bangladesh Journal of Obstetrics & Gynaecology, 2020)
Objective: To assess the level of satisfaction with caesarean delivery and to see the relationbetween different parameters and satisfaction.Materials & Methods: This cross sectional study was done in the department of Obstetrics& Gynaecology of the District Sadar Hospital, Laxmipur during the period of 1st January to30th June 2017. A total of 423 post-caesarean women were included in the study. Thestructured questionnaires were used for the collection of data from the patients and the datawere processed and analyzed with the help of software SPSS.Results: During the study period, among the 465 caesarean delivery 423 were enrolledfor the study. The mean age of the patients was 23.99±5.29 years and mean parity was1.22±1.27. Initial negative reaction to the decision of caesaren section was expressed by71.9% of the patients, 18.4% remained indifferent and 9.7% showed positive reaction. Themajor reasons of initial negative reaction were fear of death and dislike of caesareansection. The satisfaction following caesarean delivery was significantly associated withage, educational status and initial positive and negative reaction to the decision of caesareansection. Three hundred and fifty five (83.9%) women expressed their overall satisfactionfollowing caesarean section.Conclusion: Most patients expressed their overall satisfaction to caesarean delivery.Bangladesh J Obstet Gynaecol, 2018; Vol. 33(2) : 101-106